Building equitable health partnerships: addressing racial disparities in global health - Bonnechère, Bruno (Frontiers in Public Health, 2025)
The traditional paradigms in global health, often characterized by power imbalances similar to the racial disparities between White and Black populations, are insufficient for addressing the complex health challenges of the 21st century. These disparities not only exist within national borders but also mirror the limitations of the North–South paradigm on an international scale. This framework perpetuates systemic inequalities, undermines local agency, and neglects the valuable expertise within communities of color. The evolving landscape of global health, marked by emerging infectious diseases, antimicrobial resistance, non-communicable diseases, and climate change impacts, necessitates a paradigm shift toward partnerships based on mutual respect, shared responsibility, and equitable collaboration. This paper explores the limitations of the conventional paradigms and highlights the multifaceted benefits of a more collaborative approach. It demonstrates how equitable partnerships can enhance health security, foster innovation, and promote sustainable development across racial lines. Successful examples of equity-focused cooperation illustrate the potential of diverse partnerships in strengthening health systems and promoting knowledge sharing between White and Black communities. A new framework for health cooperation is proposed, emphasizing mutual respect, transparency, accountability, and sustainable capacity building. By recognizing the agency and expertise of Black communities, we can create a more inclusive and democratic health architecture. This shift from a charity-based mindset to one rooted in solidarity acknowledges that investing in health equity is a strategic investment in our collective future. Embracing this interconnected approach will enable us to tackle pressing racial health challenges and ensure a healthier and more equitable future for all.